Dampak Guru Berlatarbelakang Pendidikan Berbeda dalam Keberhasilan Belajar Siswa - Fahruddin, Zuhri (Tarqiyatuna: Jurnal Pendidikan Agama Islam dan Madrasah Ibtidaiyah, 2022)
The purpose of this research is to find out which teachers have different backgrounds in student learning success, it is mentioned in the educational background here that they are teachers with PAI and non-PAI backgrounds, non-PAI who are meant to be teachers with a background in Da'wah Science. The sampling technique used isCensus Samples (Saturated Sample), while criterion-based selection is used when conducting qualitative research.The data sources were teachers with a background of Da'wah, as informants in the first phase of research, students and teachers with educational backgrounds in stage II research. The number of informants and respondents in this study were 2 teachers, 30 students,Data collection techniques using in-depth interviews, observation, and documentation. Qualitative data analysis uses interactive analysis techniques, namely the interaction of three components, namely data reduction, data presentation, drawing conclusions and verification. Quantitative data analysis used descriptive statistical analysis. The expected result is that it can contribute to teachers in formal and non-formal school institutions in the small or large scope.